Analysing the influence of firm size on financial performance in Malaysian ICT sector - Lim, Brenda Xun Li (2018)
This empirical study examines the influence of firm size on the financial performance of Malaysian Information and Communication Technology (ICT) listed companies. The study utilised a sample of 53 of ICT listed companies derived from the Osiris database for the period covering 2008- 2012. The independent variable is firm size, which is measured by proxies such as total assets, market capitalisation and total sales, while the dependent variables, firm financial performance, is measured by profitability ratios (return on assets (ROA), return on equity (ROE), profit margin). Based on the review of literature in this study, the conceptual framework was proposed and the hypotheses of this study were developed to examine the relationship between the variables of firm size and firm financial performance. Besides, the multiple regression analysis was used in analysing the data collected in this study. The finding of the study showed that finn size, which used the proxy of total asset, market capitalisation and total sales, has a significant effect on firm financial performance in terms of ROE. On the other hand, there is no significant effect in the result between firm size and firm performance in terms of ROA and profit margin. The study concluded that it provides a useful insight to different users, who can benefit from the financial information and assist them in their decision making processes by understanding the nature of the firms' size and financial information in evaluating the firms' performance. On this ground, the study recommended that the government or firms should implement a guideline that provides comprehensive financial information for various entities. This in tum will provides a better evaluation and qualitative judgment on companies' financial -performance.